Physicochemical structure characteristics and intrinsic reactivity of demineralized coal char rapidly pyrolyzed at elevated pressure. Issue 3 (June 2020) - Lin, Dan; Liu, Li; Zhao, Yi-Jun; Zhao, Yan; Qiu, Peng-Hua; Xie, Xing; Sun, Shao-Zeng
Abstract: This study aims to investigate the effect of pyrolysis pressure on the physical and chemical structure characteristics and reactivity of subbituminous demineralized coal char. The pyrolysis experiments were studied under different pressures using a pressurized drop tube reactor (PDTR). Structural properties of coal chars were investigated by the application of scanning electron microscopy (SEM), nitrogen adsorption analyzer, automatic mercury porosimeter, and Raman spectroscopy, respectively. The Random Pore Model was used to determine kinetic parameters and intrinsic reactivity of chars. The specific pore volume of chars pyrolyzed at 900–1000 °C increased first and then decreased with pyrolysis pressure increasing, and the maximum value of the specific pore volume of chars occurred at 1.0 MPa. The degree of graphitization of chars deepened with the increase of temperature or pressure. Intrinsic activation energy of char-O2 was within the range of 126–134 kJ/mol. The intrinsic reactivity of char-O2 reaction showed strong correlation the Raman parameters with the change of pyrolysis conditions, and it suggested that the intrinsic reactivity of char-O2 reaction was mainly affected by aromatic ring structures rather than pore structures. Highlights: Effect of pyrolysis pressure on demineralized char structure and reactivity was investigated. Pore volume of chars increased first and then decreased with pressure increasing over 900 °C. Elevated pressure made contribution to the graphitization of demineralized chars. Effect of pressure on intrinsic reactivity of chars emerged at pyrolysis temperature over 900 °C. Intrinsic reactivity of chars was mainly affected by chemical structure rather than pore structure.